2014
DOI: 10.1017/s1479262114000707
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in African yam bean accessions based on AFLP markers: towards a platform for germplasm improvement and utilization

Abstract: Accurate knowledge of intra-specific diversity of underutilized crop species is a prerequisite for their genetic improvement and utilization. The diversity of 77 accessions of African yam bean (AYB, Sphenostylis stenocarpa) was assessed by amplified fragment length polymorphism (AFLP) markers. A total of EcoRI/MseI primer pairs were selected and 227 AFLP bands were generated, of which 59(26%) were found to be polymorphic in the 77 accessions of AYB. The most efficient primer combination for polymorphic detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 28 publications
3
23
0
Order By: Relevance
“…In the work carried out by Ojuderie et al (2014), the Bangladesh accession grouped together with the two accessions of Ghana origin. Moreover, the clustering of accessions in the present research was not on the basis of geographical origins and this concur with previous reports (Moyib et al , 2008; Adewale et al , 2014). This result seems to suggest high exchange of AYB germplasm among smallholder farmers across regions.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the work carried out by Ojuderie et al (2014), the Bangladesh accession grouped together with the two accessions of Ghana origin. Moreover, the clustering of accessions in the present research was not on the basis of geographical origins and this concur with previous reports (Moyib et al , 2008; Adewale et al , 2014). This result seems to suggest high exchange of AYB germplasm among smallholder farmers across regions.…”
Section: Discussionsupporting
confidence: 93%
“…The research conducted by Moyib et al (2008) using RAPDs revealed considerable genetic diversity among 24 AYB accessions. Furthermore, AFLPs analysis presented a high level of diversity among AYB accessions (Adewale et al , 2014; Ojuederie et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, it is chiefly grown as an annual, but has received some attention as a perennial component in annual intercropping systems in place of the non-food producing leguminous trees (like Leucaena) typically used in arid alley cropping (Daniel and Ong, 1990;Waldman et al, 2017). The African yam bean (Sphenostylis stenocarpa Harms) is an interesting crop in that it is grown for both its beans (which can be harvested perennially), and its large edible tuber (thus ending its life); this underutilized crop is being studied for traits and genetic markers to assist in breeding (Adewale et al, 2012(Adewale et al, , 2015. Finally, the protein category also includes alfalfa (Medicago sativa) and stinging nettle (Urtica dioica) for their leaf protein concentrate (LPC), a tofu-like product created by deriving protein-rich curds from leaf juice or pulp.…”
Section: Characteristics and Yields Of Perennial Staple Cropsmentioning
confidence: 99%
“…A number of underutilised crops have significant potential, particularly within systems where their nitrogen fixation abilities can play a major role in enhancing soil fertility for other crops. For example, African yam bean is a leguminous crop which is considered to have considerable unrealised potential to contribute to food security in many parts of sub-Saharan Africa (Adewale et al, 2015). However, as with many 'orphan' crops there is a lack of good data about current production and usage.…”
Section: Genetic Resources In the Humid Tropicsmentioning
confidence: 99%